Small mesh nets protect tomato plants from insect pests and increase yields in eastern Africa. Issue 2 (3rd March 2020) - Nordey, Thibault; Deletre, Emilie; Mlowe, Nickson; Martin, Thibaud
ABSTRACT: The cultivation of vegetables under tunnels is considered a promising alternative to the use of chemicals to manage insect pests. However, higher temperatures under covers hinder their use in warm regions. We investigated the effect of high tunnels covered with plastic film or small or large mesh insect-nets on the performances of tomato plants in Tanzania over two years. Control plants were grown in open field plots. The temperature during the day was 4°C and 15°C higher under the nets and under the plastic than in the open. The total number of insect pests per plant over the season was generally lower under the nets than in open, with the small mesh better than the large mesh. The nets promoted plant growth compared with the open plots, with higher leaf area, plant dry weight, and plant height. Marketable yields were lower in open (2.7 and 10.8 t.ha −1 ), intermediate under the large mesh (7.9 and 38.4 t.ha −1 ), and high under the small mesh (16.8 and 50.1 t.ha −1 ). Higher productivity under the nets was associated with better plant growth and fewer insects than in the open. Contrasting results could be obtained in warmer climates because of the increase in temperatures recorded under tunnels.